Gluxsystem: Real-Time Monitoring of Diabetic Wounds Using an App-Iot Integrated Hydrogel Patch - Azizah Nur Sya'bani; Dea Ocha Nerissa Arviana; Raudhah (Writing Center IMERI FMUI, 2025)
Introduction: Diabetes mellitus is a metabolic disorder associated with severe complications, including diabetic foot ulcers (DFU). The World Health Organization estimates that more than 830 million people worldwide are affected. DFU remains a leading cause of infection, amputation, and mortality, largely due to delayed detection of changes in the wound microenvironment. Objective: This study presents a theoretical design and conceptual framework for GLUXSYSTEM, an intelligent hydrogel-based patch integrating pH and glucose sensing with an application–IoT platform for non-invasive monitoring of diabetic wounds. Methods: The proposed sensing mechanisms are derived from established biochemical principles. pH sensing is conceptualized using a chitosan hydrogel containing glycerol and Bromothymol Blue (BTB), in which colorimetric changes result from pH-dependent protonation of the indicator. Glucose sensing is modeled using a PEGDA–APBA hydrogel embedded in a photonic crystal, in which glucose binding induces hydrogel swelling and structural color shifts. The system architecture envisions optical signal capture via a smartphone application for cloud-based data interpretation. Results: As a design-based study, the system is projected to produce distinguishable colorimetric responses corresponding to wound conditions. Based on the underlying chemical models, pH changes from acidic to alkaline would generate yellow-to-blue transitions, while increasing glucose concentration would produce structural color shifts from blue to purple and pink. These theoretical responses are consistent with reported associations between elevated pH/glucose levels and DFU severity. Conclusion: GLUXSYSTEM offers a conceptual, non-invasive approach to wound monitoring. While this study focuses on the design and integration framework, it provides a necessary foundation for future experimental validation and the development of accessible digital solutions in diabetic wound care.